2012
DOI: 10.1088/0029-5515/52/5/054010
|View full text |Cite
|
Sign up to set email alerts
|

On the confinement of passing alpha particles in a tokamak-reactor with resonant magnetic field perturbations shielded by plasma currents

Abstract: Alpha-particle losses due to the resonant magnetic field perturbations (RMPs) created by the coil system for Edge Localized Mode mitigation in ITER are studied numerically. If shielding of RMPs by the plasma is not taken into account, passing α-particles are the main loss channel which, together with the trapped particle contribution leads to a loss of more than 5 % of fusion alpha particle power. Shielding of RMPs practically eliminates this channel so that the overall losses are reduced to about 1 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This work focuses on the low toroidal mode number ( = − n 2 3) helical magnetic perturbations typically used for such things as edge-localized mode (ELM) control. Similar coils have been predicted to cause 5% or more loss of neutral beam ions in ITER plasmas [5][6][7][8][9][10], making the accurate and validated modeling of this interaction a priority. Of course, understanding how well fast ions are confined and where they go if lost due to externally applied 3D fields is a key part of not only predicting the performance and ensuring safe operation of future devices, but key for understanding, interpreting, and optimizing experiments on current devices.…”
Section: Introductionmentioning
confidence: 93%
“…This work focuses on the low toroidal mode number ( = − n 2 3) helical magnetic perturbations typically used for such things as edge-localized mode (ELM) control. Similar coils have been predicted to cause 5% or more loss of neutral beam ions in ITER plasmas [5][6][7][8][9][10], making the accurate and validated modeling of this interaction a priority. Of course, understanding how well fast ions are confined and where they go if lost due to externally applied 3D fields is a key part of not only predicting the performance and ensuring safe operation of future devices, but key for understanding, interpreting, and optimizing experiments on current devices.…”
Section: Introductionmentioning
confidence: 93%
“…The quasilinear transport coefficients (49) are determined by the RMP electromagnetic field in the vicinity of the resonant surface. The estimate of this field for real tokamak geometry is obtained using the method similar to the one used in [11,28]. Presenting the total tokamak field as a sum of the axisymmetric equilibrium field and the perturbation field, B = B 0 + B 1 , these fields are expressed through vector potentials in symmetry flux coordinates (ψ tor , ϑ, ϕ) as follows:…”
Section: Relation To Real Geometrymentioning
confidence: 99%
“…(It should be noted that these form factors do not tend to a constant value at the inner flux surfaces outside the resonant layer because B r(plas) m (r) still satisfies there the ideal MHD equation of [29], see [6].) This method has been used in [11,28] and is used here for estimation of the shielding effect on the perturbed magnetic field topology. Conversely, the transport coefficients (49) computed for the separate perturbation field modes m for the straight cylinder model are multiplied upon the summation with spectral weights given by…”
Section: Relation To Real Geometrymentioning
confidence: 99%
“…This is of special importance for future burning plasmas with a large content of MeV-ions with relatively long slowing-down times. Numerical simulations of fast-ion losses induced by ELM mitigation coils in ITER [5][6][7][8][9] have shown that, under certain conditions, up to 20% of the neutral beam injection (NBI) power can be lost due to the 3D fields created by the ELM mitigation coils. An experimentally validated model for the plasma response is, however, needed to improve our abilities to make realistic predictions for ITER as the plasma can shield or even amplify some components of the externally applied MPs leading to a complex 3D background equilibrium.…”
Section: Introductionmentioning
confidence: 99%